Nearshoring strategy to boost Islamic banking and finance in Bosnia & Herzegovina - Omercic, Jasmin (Islamic Finance News, 2023)
The greatest obstacles Bosna Bank International (BBI) has faced are not just within but outside the country such as COVID-19, geopolitics, economic instabilities and climate change. Notwithstanding all these obstacles, BBI has made considerable efforts to boost the overall economy including the development of Islamic activities in Bosnia & Herzegovina (B&H). One of the initiatives is assessing the strategy of nearshoring as a distinct business accelerator to propel renowned multinational corporations, manufacturers, logistical powerhouses, etc, to have their headquarters or branches in B&H.